A case study on product labeling in Kuching city / Noor Lela Said Mohamad - Said Mohamad, Noor Lela (2009)
The purpose of this study is to determine the effectiveness of product labeling, to examine the information on the product package, to examine the customer awareness and also to identify the customer satisfaction on product labeling in Kuching City. Product labeling plays the most important role in marketing system to ensure that the product is presentable in a customized and standardized patterns which includes the informations like pictures of the products, features, design, content of the ingredients, size information, warnings of the products and many more. Labels are also widely used as an identification with words or ideas attached to products. It also regulates the presentation of a specific information and instructions to consumers. From the findings of the analysis, it seems that majority of the respondents come from female buyers compared to men. This indicates that female are more aware of the product labels whether it has misleading information or not and perhaps they absolutely satisfied with the product labels. Thus, they will be influenced with the quality labeled products which satisfy their perceptions, expectations and will increase their loyalty.